Research on the fabrication and evaluation of certain properties of the multi-metallic catalyst supported on silica TeKL-25 - Nguyen, Dinh Hung; Vu, Ngoc Toan; Nguyen, Van Hoang; Nguyen, Hong Son; Luong, Trung Thien; Le, Quang Minh; Tran, Minh Anh (Journal of Military Science and Technology, 2025)
This paper presents the research results on the synthesis of the multi-metallic catalyst material TeKL-25 based on a silica support. The characteristics of the synthesized material were analyzed using advanced techniques such as Field Emission Scanning Electron Microscopy (FE-SEM), Brunauer-Emmett-Teller (BET) surface area analysis, X-ray Diffraction (XRD), and Energy Dispersive X-ray Spectroscopy (EDX). The synthesized TeKL-25 material exhibits a tightly bonded structure, a rough surface, relatively uniform particle distribution, a BET surface area of 292.716 m2/g, and a mesoporous structure.